Heterogeneity and Potency of Peripheral Glial Cells in Embryonic Development and Adults - Sinegubov, Artem; Andreeva, Daria; Burzak, Nikita; Vasyutina, Maria; Murashova, Lada; Dyachuk, Vyacheslav (Frontiers in Molecular Neuroscience, 2022)
This review describes the heterogeneity of peripheral glial cell populations, from the emergence of Schwann cells (SCs) in early development, to their involvement, and that of their derivatives in adult glial populations. We focus on the origin of the first glial precursors from neural crest cells (NCCs), and their ability to differentiate into several cell types during development. We also discuss the heterogeneity of embryonic glia in light of the latest data from genetic tracing and transcriptome analysis. Special attention has been paid to the biology of glial populations in adult animals, by highlighting common features of different glial cell types and molecular differences that modulate their functions. Finally, we consider the communication of glial cells with axons of neurons in normal and pathological conditions. In conclusion, the present review details how information available on glial cell types and their functions in normal and pathological conditions may be utilized in the development of novel therapeutic strategies for the treatment of patients with neurodiseases.